IMPLEMENTING DATA ANALYSIS IN SMALL BUSINESSES - Fernando Pacheco, Leonardo; Gomes dos Santos, André (Journal of Interdisciplinary Debates, 2023)
This article aims to address the topic of data analysis, providing a comprehensive overview of the concept, techniques, and methods of utilization, as well as examples of possible applications. Although the field of Data Science is relevant to companies and businesses of all sizes, this article will focus its efforts on highlighting the specific importance and relevance of this discipline for small businesses. In this regard, an accessible and easily understandable language will be explored, with the intention of simplifying the methods of application and facilitating the assimilation of this knowledge by entrepreneurs and managers of small businesses. Practical examples of how data analysis can be implemented in different areas such as marketing, sales, operations, and strategic decision-making will be addressed. Additionally, the direct and indirect benefits that small businesses can obtain by adopting a data-driven approach will be discussed.